HUBUNGAN SEGITIGA NAGEL DENGAN SEGITIGA ASALNYA - Reni Widya; Hasriati '; M. Natsir (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This paper discusses the relationship between the Nagel triangle and the originaltriangle. The Nagel triangle is formed by connecting the three of tangent points of theexcircle to the sides of the triangle. This relationship can be shown through thecollinearity of centroid and incenter of the original triangle to Nagel point of the Nageltriangle. Then, the relationship between the area of the Nagel triangle and the area of theoriginal triangle is shown.